Teologi Pengharapan Jürgen Moltmann dan Sumbangannya bagi Moral Sosial Katolik: Sebuah Refleksi Pasca Kunjungan Paus Fransiskus ke Indonesia - Prastiyo, Ferdian Dwi (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
Every religion has a duty and vocation to contribute to the common good. This duty and vocation is lived through a way of life that is not separated from the context of people's lives. Religion that exists in this way is able to bring hope to the world. Jürgen Moltmann reflects on this religious duty and vocation with the idea of a theology of hope. Hope is based on the idea of eschatology. Moltmann asserts that God is involved in the history of the world. The center of hope is the crucified God, a God who is involved in and sympathetic to the concerns of humanity. Moltmann then emphasized that the Church needs to always present a messianic, relational, and populist side. Moltmann's idea of hope can be one of the inspirations in reflecting on the call of Pope Francis during his visit to Indonesia and to reflect on the Ordinary Jubilee Year 2025. The Church in Indonesia needs to grow by faithfully encountering the people, being inculturated, and having a macro view of life together.